Clinical Profile and Management of Patients with Newly Diagnosed Type 2 Diabetes Mellitus in Hospital Setting - Diego Muñoz Moreno; Gilberto Pérez López; Luis Antonio Álvarez-Sala Walther; José Antonio Rueda Camino; Javier Martín Vallejo; Olga González Albarrán (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: New-onset type 2 diabetes mellitus (T2DM) is a common clinical scenario in the hospital settings. However, data on the baseline characteristics of these patients at diagnosis in Spain remain limited. Objectives: This study aims to describe the characteristics of 165 patients admitted to a Spanish tertiary hospital with new-onset T2DM. We analysed the use of different treatment regimens at discharge and metabolic control during follow-up. Methods: A retrospective, single-centre cohort study was conducted at General University Gregorio Marañón Hospital, between January 2018 and April 2021. Results: A total of 165 patients participated, with a mean age of 56.4 years, 62.4% of whom were men. Diabetes-related complications were observed in 24.8% of patients at diagnosis. Combined antidiabetic treatment was required in 87% of cases. The mean baseline HbA1c was 10.8%, which decreased by 4.9% after 8 months of follow-up. Conclusion: The clinical heterogeneity and severity of hyperglycaemia in this cohort presented management challenges, in contrast to outpatient settings. Monotherapy was rarely used, with higher adoption of SGLT-2 inhibitors and GLP-1 receptor agonists compared to other studies. Additional research is needed to refine treatment strategies and optimize care for patients with newly diagnosed T2DM.